New cytotoxic constituents from the Red Sea soft coral Nephthea sp. Issue 11 (2nd June 2016) - Hegazy, Mohamed-Elamir F.; Gamal-Eldeen, Amira M.; Mohamed, Tarik A.; Alhammady, Montaser A.; Hassanien, Abuzeid A.; Shreadah, Mohamed A.; Abdelgawad, Ibrahim I.; Elkady, Eman M.; Paré, Paul W.
Abstract : Nephthea are soft coral species rich in sesquiterpenoids and steroids. An organic extract of Nephthea sp. resulted in the isolation of a new steroid (1 ), as well as several previously reported metabolites (2 –9 ). Structures were elucidated by employing NMR and HR-EI-MS analyses. The total extract, fractions and purified compounds exhibited differential cytotoxicity against the breast cancer MCF-7 cell line. Abstract :